The REDS score: a new scoring system to risk-stratify emergency department suspected sepsis: a derivation and validation study - Narani Sivayoham; Lesley A Blake; Shafi E Tharimoopantavida; Saad Chughtai; Adil N Hussain; Maurizio Cecconi; Andrew Rhodes (BMJ Open)
Objective To derive and validate a new clinical prediction rule to risk-stratify emergency department (ED) patients admitted with suspected sepsis.Design Retrospective prognostic study of prospectively collected data.Setting ED.Participants Patients aged ≥18 years who met two Systemic Inflammatory Response Syndrome criteria or one Red Flag sepsis criteria on arrival, received intravenous antibiotics for a suspected infection and admitted.Primary outcome measure In-hospital all-cause mortality.Method The data were divided into derivation and validation cohorts. The simplified-Mortality in Severe Sepsis in the ED score and quick-SOFA scores, refractory hypotension and lactate were collectively termed ‘component scores’ and cumulatively termed the ‘Risk-stratification of ED suspected Sepsis (REDS) score’. Each patient in the derivation cohort received a score (0–3) for each component score. The REDS score ranged from 0 to 12. The component scores were subject to univariate and multivariate logistic regression analyses. The receiver operator characteristic (ROC) curves for the REDS and the components scores were constructed and their cut-off points identified. Scores above the cut-off points were deemed high-risk. The area under the ROC (AUROC) curves and sensitivity for mortality of the high-risk category of the REDS score and component scores were compared. The REDS score was internally validated.Results 2115 patients of whom 282 (13.3%) died in hospital. Derivation cohort: 1078 patients with 140 deaths (13%). The AUROC curve with 95% CI, cut-off point and sensitivity for mortality (95% CI) of the high-risk category of the REDS score were: derivation: 0.78 (0.75 to 0.80); ≥3; 85.0 (78 to 90.5). Validation: 0.74 (0.71 to 0.76); ≥3; 84.5 (77.5 to 90.0). The AUROC curve and the sensitivity for mortality of the REDS score was better than that of the component scores. Specificity and mortality rates for REDS scores of ≥3, ≥5 and ≥7 were 54.8%, 88.8% and 96.9% and 21.8%, 36.0% and 49.1%, respectively.Conclusion The REDS score is a simple and objective score to risk-stratify ED patients with suspected sepsis.